Insecticidal and Enzyme Inhibitory Activities of Sparassol and Its Analogues against Drosophila suzukii - Kim, Junheon; Jang, Miyeon; Lee, Kyoung-Tae; Yoon, Kyungjae Andrew; Park, Chung Gyoo (Journal of agricultural and food chemistry, 2016)
Drosophila suzukii is an economically important pest in America and Europe as well as in Asia. Sparassol and methyl orsellinate are naturally produced by the cultivating mushrooms Sparassis cripta and Sparassis latifolia. Fumigant and contact toxicities of synthetic sparassol and its analogues, methyl orsellinate and methyl 2,4-dimethoxy-6-methylbenzoate (DMB), were investigated. Negligible fumigant activity was observed from the tested compounds. However, DMB showed the strongest contact toxicity, followed by sparassol and methyl orsellinate. The possible modes of action of the compounds were assessed for their acetylcholinesterase (AChE)- and glutathione S-transferase (GST)-inhibiting activities. AChE activity was weakly inhibited by methyl orsellinate and DMB, but GST was inhibited by sparassol, methyl orsellinate, and DMB. Thus, DMB could be a promising alternative to common insecticides as it can be easily synthesized from sparassol, which is the natural product of Sparassis species. Sparassis species could be an industrial resource of DMB.